2015
DOI: 10.1007/s00404-015-3812-0
|View full text |Cite
|
Sign up to set email alerts
|

New perineal injection technique for pudendal nerve infiltration in diagnostic and therapeutic procedures

Abstract: Perineal pudendal injection is an effective and safe technique for anesthesia in diagnostic (vulva biopsy) and therapeutic indications (pudendal neuralgia), and regional anesthesia in perinatal settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Image-guided or finger-guided PNIs can be performed according to the experience of the physician, adequate equipment presence, and patient choice. Over the past 20 years, studies have described the PNI techniques [14][15][16][17][18][19][20], but a limited number of studies have compared the efficacy of image-guided PNI techniques [21]. To the best of our knowledge, there are no studies comparing the finger-guided transvaginal PNI (TV-PNI) and ultrasound (US)-guided transgluteal PNI (TG-PNI) for the evaluation of pain relief in patients with PN.…”
Section: Introductionmentioning
confidence: 99%
“…Image-guided or finger-guided PNIs can be performed according to the experience of the physician, adequate equipment presence, and patient choice. Over the past 20 years, studies have described the PNI techniques [14][15][16][17][18][19][20], but a limited number of studies have compared the efficacy of image-guided PNI techniques [21]. To the best of our knowledge, there are no studies comparing the finger-guided transvaginal PNI (TV-PNI) and ultrasound (US)-guided transgluteal PNI (TG-PNI) for the evaluation of pain relief in patients with PN.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior approach has been used in recent years in proximal nerve entrapment syndrome, with a high rate of success in terms of the diagnostic/therapeutic objective, although with a moderate 21.7% risk of sacral plexus blockade. 2 Techniques for pudendal nerve blocks described include: 1. anatomical landmarks 15 ; 2. neurostimulation 6,66 ; 3. fluoroscopy 49 ; 4. tomography [67][68][69] ; and, more recently, blockage guided by ultrasound. 1,7,49,59,[70][71][72] We believe that ultrasound is better than other techniques in terms of practical use and results 71 and, therefore, we will focus on the sonoanatomic descriptions that enable a refined and reproducible practice in order to increase the frequency of success in terms on the specific goals proposed for each individual patient.…”
Section: Pudendal Nerve Anatomymentioning
confidence: 99%
“…14 Moreover it is an integral part of the diagnosis and therapy of pudendal neuropathy of which little is known, although there is growing research into its pathophysiology and therapeutic approaches. 2,[14][15][16][17][18][19][20] Despite the above, pudendal nerve blocks are not a popular technique in daily practice in general, urologic or obstetric surgery, perhaps because of lack of knowledge of the block or because of the frequency of blind blocks with variable or incomplete results. 8 At present, with the popularity of ultrasound-guided blocks [21][22][23][24][25][26][27][28][29][30][31][32] it is important to review the anatomy, sonoanatomy and some relevant technical aspects that may make its implementation a safe and reproducible practice.…”
Section: Introductionmentioning
confidence: 99%
“…Different routes of injections, and various types of image-guided pudendal nerve injection (PNI) techniques, which intend to in ltrate local anesthetic agents within proximity to the corresponding nerve, were described previously [14][15][16][17][18][19]. Recently, our pelvic pain workgroup reported that nger-guided transvaginal PNI might be an alternative approach to the ultrasound-guided technique, as a safe and effective treatment for PN management [15].…”
Section: Introductionmentioning
confidence: 99%